Organizing on two wheels: uncovering the organizational patterns of Hells Angels MC in Sweden - Rostami, Amir (Trends in organized crime)
During the last decades, Outlaw Motorcycle Clubs (OMCs) have become a concern for crime prevention and law enforcement agencies. The general perception of OMCs is ambiguous. They are seen either as highly structured criminal organizations whose members use their motorcycle clubs for conducting sophisticated criminal enterprises, or as clubs built around the camaraderie of freedom-seeking bikers. Using unique Swedish longitudinal data on gang membership and co-offending patterns, we study the organizational dynamics of Hells Angels MC Sweden and its sub-organizations Red & White Crew and Red Devils MC. Our results reveal a complex picture. Co-offending network patterns and offense type distributions vary for each sub-organization, indicating potential differences in organizational dynamics. Red & White Crew has features that are more similar to street gangs than OMCs, and Red Devils MC has a more decentralized and chapter-based pattern of criminal collaboration than Hells Angels MC. Besides increasing our understanding of OMC collaboration structure, our results have implications for crime prevention strategies. We suggest that social responses and law enforcement efforts should take into account the heterogeneity of OMCs in order to avoid counterproductive consequences in terms of increased group cohesiveness.